Lecturer Forecasting and Professor Acceleration using Bussiness Intelligence - Bambang Sundari Tamtosutrisno; Helmy Fitriawan; Mardiana Mardiana (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2023)
Universities must be allowed to compete and increase public accountability and competitiveness in order to enhance the quality of education. Human resources, such as professors and educational staff, are one of the supporting aspects. Lecturers are one of the most significant markers for gauging the viability and quality of academic programs and postsecondary institutions. Lecturer data evolves according to educational level, functional position and tenure (retirement) which need to be monitored and anticipated as data to help strategic planning for the next few years to improve the quality and accountability of a tertiary institution. Data sources that are validated and linked with legally authorized data sources are required to support business intelligence in the decision-making processes of policymakers and institutional leaders.